Promoting Renewable Energy through Auctions : The Case of China - Wang, Xiaodong; Barroso, Luiz; Elizondo, Gabriela (World Bank, Washington, DC, 2014)
This knowledge note singles out auctions as an important mechanism that has been implemented in a growing number of countries in recent decades. It features a case study of auctions designed to promote the generation of electricity from renewable sources in China. Although feed-in tariffs are now the cornerstone of China's renewable energy policy, auctions have played and continue to play a role in identifying market prices for renewable energy in the country. Experience with the auctioning of wind and solar concessions enabled the Chinese authorities to modify auctions over time to yield accurate information about the costs of generation from renewable sources, allowing them to set feed-in tariffs at efficient levels. This case study is interesting, because China has set aggressive renewable energy targets and introduced policy incentives for rapid market development. Initial renewable energy prices showed significant variation, and the government s targets were not achieved prior to 2005. The most important milestone in the development of renewable energy in China was the 2005 Renewable Energy Law. China has applied successive adjustments to concessions auctions to improve their usefulness in setting appropriate feed-in tariffs. The key lesson from China's experience with auctioning of concessions is that winning bid prices that are lower than actual costs wind up deterring the development of renewable energy.